♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
To find the x-intercept ;
Just need to put 0((zero)) instead of y in the equation.
Let's do it....
3x - 7y = 21
3x - 7(0) = 21
3x - 0 = 21
3x = 21
Divided sides by 3
3 / 3 × x = 21 / 3
x = 7
Thus the x-intercept is 7 .
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
To find the y-intercept ;
Just need to put 0((zero)) instead of x in the equation.
Let's do it....
3x - 7y = 21
3(0) - 7y = 21
0 - 7y = 21
-7y = 21
Divided sides by -7
-7 / -7 × y = 21 / -7
y = - 3
Thus the y-intercept is -3.
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️